Dragons eat noodles on Tuesdays - Stahl, Jon; Bentley, Tadgh (New York : Scholastic Press, 2019)
While two monsters argue over how the story they are telling should go, Dennis, a very hungry dragon, is listening nearby--and he has very definite ideas about how this story should end.
AD360L
Decoding demand: 75 (high) Semantic demand: 73 (high) Syntactic demand: 34 (low) Structure demand: 81 (very high)
Accelerated Reader AR
Keywords: Dragons -- Juvenile fiction; Monsters -- Juvenile fiction; Storytelling -- Juvenile fiction; Storytelling -- Fiction; Humorous fiction